Turtle comes out of her shell : a book about feeling shy - Graves, Sue, 1950-; Dunton, Trevor (New York, NY : Franklin Watts, an imprint of Scholastic Inc., 2022)
Turtle is kind and helpful, but often very shy, and with the class talent show coming up she will need to overcome her shyness because everybody wants to hear her beautiful voice singing with Little Bear.
2.6
K-3
AD480L
Keywords: Turtles -- Juvenile fiction; Animals -- Juvenile fiction; Bashfulness -- Juvenile fiction; Singing -- Juvenile fiction; Turtles -- Fiction; Animals -- Fiction; Bashfulness -- Fiction; Singing -- Fiction; Animal fiction